2004
DOI: 10.1111/j.1746-1561.2004.tb07935.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of School Nurse Case Management on Students with Asthma

Abstract: This project determined asthma prevalence in a large school district, absentee rates, and potential effects of school nurse case management for student asthma over three years. Data were derived from an asthma tracking tool used by nurses in one school district for every student reported as having asthma by their parent. School nurses began collecting data in their schools in 1999-2000 when an asthma-management protocol was first developed. Nurses documented perceived asthma severity for each student, presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 16 publications
2
57
0
Order By: Relevance
“…The finding that illness absences among students with asthma were reduced following asthma screening and referral for care mirrors the finding that when a consulting physician was used in a school asthma absence program, absence was reduced by 1 day annually (Wilson et al, 2009). The improvement in asthma action plans and medication at school for asthmatic children seen in this study is similar to the findings of Taras, Wright, Brennan, Campana, and Lofgren, (2004), although their study did not demonstrate a reduction in absenteeism among these students. Levy, Heffner, Stewart, and Beeman (2006) found that intensive CM for asthma students including asthma education, absence of follow-up, and coordination of student's asthma care resulted in ''.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that illness absences among students with asthma were reduced following asthma screening and referral for care mirrors the finding that when a consulting physician was used in a school asthma absence program, absence was reduced by 1 day annually (Wilson et al, 2009). The improvement in asthma action plans and medication at school for asthmatic children seen in this study is similar to the findings of Taras, Wright, Brennan, Campana, and Lofgren, (2004), although their study did not demonstrate a reduction in absenteeism among these students. Levy, Heffner, Stewart, and Beeman (2006) found that intensive CM for asthma students including asthma education, absence of follow-up, and coordination of student's asthma care resulted in ''.…”
Section: Discussionsupporting
confidence: 89%
“…The literature suggests school aged children with asthma experience more hospitalizations, decreased overall activity, more night-time cough, and sleep disturbances when compared to their healthy classmates (CDC, 2007; McCann, McWhirter, Colemean, Devall & Calvce, 2002;Taras, Wright, Brennan, Campana & Lofgren, 2004). In addition, several studies have demonstrated a relationship between asthma and decreased involvement in exercise and physical activities among school aged children (Lang, Butz, Duggan & Serwint, 2004;Mansour et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a school where CM was instituted, intervention students in Years 1 and 2 of the program were more likely to have medications and PF measured at school during the following year; however, severity classifications of asthma both increased and decreased as a result of CM in Years 1–2 and 2–3 (Taras, Wright, Brennan, Campana, & Lofgren, 2004). …”
Section: Resultsmentioning
confidence: 99%